Enhancing Indonesian Employees Performance through Work Facility, Soft Skill, and Work Motivation: Evidence from Indonesia - Fita Nurna Sari; Unna Ria Safitri; Xenia Nazala Syalsabila; Tien Suhartini (Politeknik Siber Cerdika Internasional, 2026)
Prior studies on the determinants of employee performance report inconsistent findings regarding work facilities, work motivation, and soft skills, revealing a research gap that this study addresses by testing all three predictors simultaneously within a single organizational context. This study examines the partial and simultaneous effects of work facilities, work motivation, and soft skills on employee performance at PT. ESGI in Boyolali, Central Java, Indonesia. An associative quantitative design was employed, with data collected from 97 employees selected through incidental sampling using a validated and reliable Likert-scale questionnaire and analyzed using multiple linear regression. The results show that work facilities have a significant negative effect on employee performance (β = −0.091; Sig. = 0.030), whereas work motivation (β = 0.377; Sig. < 0.001) and soft skills (β = 0.617; Sig. < 0.001) each have significant positive effects. Simultaneously, the three variables significantly affect employee performance (Sig. < 0.001; R² = 0.915). These findings suggest that motivational systems and soft-skill development contribute more strongly to performance than facility provision alone, offering practical implications for human resource strategy in the garment industry and a theoretical contribution to the debate on the facility-performance relationship.